Opportunities and threats for natural building using straw bale technology - Augustyńska, Agnieszka (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
In this paper, the possibilities of using straw bale technology in construction, as well as the threats that limit both its development and dissemination, have been presented. This study has also investigated the use of recyclable waste and the role of recycling in natural construction, as well as the impact of CO2 reduction on pro-ecological activities. The characteristics of natural straw construction have been discussed, and the main features of straw bale technology have been presented. Examples of the implementation of straw bale technology in both Poland and Europe have been presented and the methods of their use have been described. An integral part of this study is an overview of the opportunities and threats of the use of straw bale technology in natural construction. Low-emission technologies using biodegradable materials as well as the possibility of building nZEB and passive buildings are indicated as main advantages of the technology. The necessity of introducing legal regulations that would enable the development of natural construction using straw bale technology was indicated. Straw bale technology was created as a response to an ecological challenge for sustainable construction and has significant innovation potential.